2004
DOI: 10.1093/carcin/bgh173
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotide microarray analysis of gene expression in neuroblastoma displaying loss of chromosome 11q

Abstract: A number of distinct subtypes of neuroblastoma exist with different genetic abnormalities that are predicative of outcome. Whole chromosome gains are usually associated with low stage disease and favourable outcome, whereas loss of 1p, 3p and 11q, unbalanced gain of 17q and MYCN amplification (MNA) are indicative of high stage disease and unfavourable prognosis. Although MNA and loss of 11q appear to represent two distinct genetic subtypes of advanced stage neuroblastoma, a detailed understanding of how these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 33 publications
2
64
1
Order By: Relevance
“…Moreover, these regions of gain have also been reported in other array studies on neuroblastoma. 23,24,[28][29][30]38 Thus, although our results suggest there may be a genetic profile characteristic of nodular ganglioneuroblastoma, it would not appear to distinguish this subtype of neuroblastoma from others. In our series, there was no correlation between the total number of copy number alterations or specific gains and losses and histologic prognostic categories (favorable vs unfavorable) or patient outcome.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Moreover, these regions of gain have also been reported in other array studies on neuroblastoma. 23,24,[28][29][30]38 Thus, although our results suggest there may be a genetic profile characteristic of nodular ganglioneuroblastoma, it would not appear to distinguish this subtype of neuroblastoma from others. In our series, there was no correlation between the total number of copy number alterations or specific gains and losses and histologic prognostic categories (favorable vs unfavorable) or patient outcome.…”
Section: Discussioncontrasting
confidence: 65%
“…28,30 We next examined other regions of the genome for gains and losses using single-nucleotide polymorphism arrays to identify copy number alterations that might be specific to the nodular ganglioneuroblastoma subtype. One potential limitation of our study was that two of the eight cases were post chemotherapy, and chemotherapy might introduce additional genetic changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of 11q and gain of 17q were the sole imbalances detected in one tumor, which supports the notion that these are early events. In addition, expression microarray analysis of 11qÀ neuroblastomas has shown that rare low-stage 11qÀ tumors sometimes have global gene expression profiles that are much more similar to low-stage hyperdiploid tumors than to high-stage 11qÀ tumors, an indication that loss of 11q and gain of 17q are insufficient for the establishment of metastasis (13). It is tempting to speculate that some of the microdeletions and duplications listed in Table 1 contribute to the establishment of metastatic potential in neuroblastoma; however, the possibility that many of them are merely a consequence of global genomic instability cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormalities identified in this study are therefore not representative of the entire neuroblastoma population. Samples from the Our Lady's Hospital for Sick Children and Children's Hospital at Westmead were characterized previously for largescale chromosomal imbalances by metaphase CGH analysis (12)(13)(14)(15), whereas samples from the Children's Oncology Group have been analyzed for loss of 11q by allotyping with several different polymorphic loci (6). MYCN amplification status in each sample was also assessed by either fluorescence in situ hybridization, Southern blotting, or quantitative PCR.…”
Section: Introductionmentioning
confidence: 99%